A new erythroneurine leafhopper genus and species from Thailand (Hemiptera: Cicadellidae: Typhlocybinae) - Song, Yuehua; Li, Can (Zootaxa, 2017)
A new genus of tribe Erythroneurini from Thailand, Songana gen. nov., and a new species Songana muscula sp. n., is described and illustrated.